MINOR TRUTH OF GIRL MATH ON MENTAL ACCOUNTING PERSPECTIVE - Zahrah, Niswatin; Soeherman, Bonnie (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT The "Girl Math" trend has become widespread and viral, seemingly supporting the idea that women tend to be impulsive when shopping. This research discusses the phenomenon in the context of mental accounting. This research aims to construct a conceptual model of girl math from the mental accounting perspective. This research uses the interpretivism paradigm to explore the meaning of the reality being studied through the triangulation of interview methods, observation, and information analysis through social media, the internet, and other relevant articles. This study found that almost all-girl math trends encourage impulsive buying behavior. They have a logic and mental accounting that differ from the general rational standards. Girl math has its own rationalization. The mindset of girls math occurs due to internal and external factors. Internal factors include emotions, the availability of economic resources, and self-control. External factors include community roles, product attraction, and media framing. Girl math could become another truth, but it is merely the truth of a minority. ABSTRAK Tren “Girl Math” menjadi marak dan viral dimana tren ini seolah mendukung anggapan bahwa perempuan cenderung impulsif dalam berbelanja. Penelitian ini membahas fenomena tersebut dalam konteks mental accounting. Penelitian ini bertujuan untuk mengkonstruk sebuah model konseptual girl math dalam perspektif mental accounting. Penelitian ini menggunakan paradigma interpretivisme untuk menggali makna dari realita yang diteliti melalui triangulasi metode wawancara, observasi, dan analisis informasi melalui media sosial, internet serta artikel lain yang relevan. Penelitian ini menemukan hampir seluruh tren girl math mendorong terjadinya impulsive buying behavior. Mereka memiliki logika dan mental accounting yang berbeda dengan standar rasional umum. Girl math memiliki rasionalisasinya sendiri. Mindset girl math terjadi akibat faktor internal dan eksternal. Faktor internal meliputi emosi, kesediaan sumber daya ekonomi, dan pengendalian diri. Sedangkan faktor eksternal terdiri atas peran komunitas, atraksi produk, dan framing media. Girl math bisa saja menjadi kebenaran yang lain, namun kebenaran sebatas kebenaran minoritas.